Odorant-Binding Proteins Contribute to the Defense of the Red Flour Beetle, Tribolium castaneum, Against Essential Oil of Artemisia vulgaris - Zhang, Yuan-chen; Gao, Shan-shan; Xue, Shuang; Zhang, Kun-peng; Wang, Jing-shun; Li, Bin (Frontiers in Physiology, 2020)
Function of OBPs in insect chemodetection has been extensively studied. However, the role of OBPs in defense of insects against exogenous toxic substances remains elusive. The red flour beetle Tribolium castaneum, a major stored-grain pests, cause serious economic losses for the agricultural grain and food processing. Here, biochemical analysis showed that essential oil from Artemisia vulgaris, a traditional Chinese medicine, has a strong contact killing effect against larva of the beetle. Further, one OBP gene, TcOBPC11, was significantly induced by essential oil after exposure. RNAi against TcOBPC11 led to the higher mortality compared with the controls after the EO treatment, suggesting that it is likely associated with increasing the binding affinity of EO, leading to a decrease in sensitivity to the EO. Moreover, tissue expression profiles analysis showed that expression levels of TcOBPC11 were higher in fat body, malpighian tubule and haemolymph than in the other tissue in larvae. Developmental expression profile showed that TcOBPC11 is more abundant in late larvae and adult stage than the other developmental stages. These results indicated that TcOBPC11 may be involved in degrading of exogenous toxicant in larvae of T. castaneum. Our results provide a theoretical basis support for clarifying the degradation mechanism of exogenous toxicant and new target sites for controlling the beetle.